بینکوں کی غیر سودی پراڈکٹس اور قرض پر مبنی خدمات کی شرعی حیثیت و معیارات: Shariah Status and Standards of Non-Interest Products and Loan Based Services of Banks - Hafiz Haroon Ahmad; Rubina Kausar (International Research Journal of Arabic and Islamic Studies, 2024)
The religion of Islam is a universal and comprehensive way of life that provides guidance and satisfaction to the natural emotions and attitudes of all people of all ages. It is comprehensive in all areas of life and there are instructions in Islam related to all areas of life. The issues that have been researched so far are not only commendable but also a knowledge capital for us. In present times many areas are inviting for research according to new conditions and requirements. Islam is a complete system of life; its economics is a comprehensive system that has been applicable in all areas. In the article under review, the non-interest-bearing products used in banks are described and their shariah status is also discussed. In addition, products used in banks related to loans or anything else, have also been defined. What is the Shariah status and Shariah standards of the non-interest-bearing products common in conventional banks, how Islam has explained all this and what Islamic teachings are related to it, has been clarified from the Quran and Sunnah.